Feminismo negro e TikTok: uma interpretação através da smiótica discursiva nos conteúdos da influenciadora Andressah Catty - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This work aims to analyze how influencer Andressah Catty addresses issues of black feminism in her TikTok content. To this end, a set of methodologies was used, including content analysis (Bardin, 2011) and discursive semiotics. The theoretical framework for black feminism is based on the works of Patricia Hill Collins (2019), bell hooks (2019), Carla Akotirene (2019), Sueli Carneiro (2020), and Lélia Gonzalez (1988). Regarding black women's activism, Joice Berth (2019) is cited, and regarding the digital landscape, Issaf Karhawi (2020) and platformization (Poell, Nieborg, and Van Dijck, 2020) are used. The research corpus was defined by two videos by the influencer, published on TikTok in 2025. The videos were selected to be representative of two previously identified categories: (1) cases of racism and (2) female empowerment. The selected material was analyzed using the categories of discursive semiotics: thematization, figurativization, actorization, and tonalization. The results of the analysis revealed that Andressah Catty employs a complex discursive aesthetic, articulating between denunciations of racial violence and the valorization of black women, treating it as an act of resistance. Furthermore, it demonstrated that the influencer constructs herself as a multifaceted actor, oscillating between the human figure and the activist. The complexity of the influencer's communication, which is simultaneously political and affective, was identified. It is also concluded that Andressah Catty's discourse functions as a discursive technology that decentralizes the production of knowledge and promotes affective and practical solidarity. The discursive elements analyzed reveal that black feminism not only manifests itself on TikTok, but also uses its codes to construct an autonomous, resilient, and articulate discourse.
Black feminism and TikTok: an interpretation through discursive semiotics in the content of influencer Andressah Catty
Keywords: Feminismo negro; Influenciadores; Semiótica discursiva; Black feminism; Influencers; Discursive semiotics; CIENCIAS SOCIAIS APLICADAS